ANALISIS POTENSI EKONOMI DENGAN PENENTUAN SEKTOR BASIS ANTAR KABUPATEN DI PROVINSI SULAWESI TENGAH - Ridwan Ridwan; Any Suryantini; Irham Irham (Agro Ekonomi, 2008)
The objectives of this research are: (1) analyzing and classifying economic sectors into basic and non basic sector among districts in Central Sulawesi Province; (2) understanding characteristics of economic growth among its districts; (3) understanding the role of national and regional share among its districts. The analyses used are Location Quotient, Dynamic Location Quotient, Klassen typology, and mix and share analysis. LQ analysis result show that basic sector in Central Sulawesi are agricultural sector, electricity and water supply sector, construction sector, communication and transportation sector, and services sector. LQ analysis, at sub-district level generating agricultural sector is the basic sector for Banggai Kepulauan, Banggai, Morowali, Poso, Donggala, Tolitoli, Buol, and Parimo districts. Services sector is the basic sector for Palu, Donggala, and Tojo Una Una districts. The DLQ analysis indicating that agriculturalsector still expected as basic sector .in the future for some districts in Central Sulawesi Province. The Klassen typolgy analysis show that Morowali district is categorized as developed and fast growing region; Banggai Kepulauan, Banggai, Tolitoli, and Buol districts are categorized as growing regions; Parimo and Palu districts are categorized as growing but under-pressured; while Poso, Donggala, and Tojo Una Una districts are categorized as less developed The mix and share analysis shows that the regional share of 10 districts are more prominent determinant factor than national share.